Antenna driver and control for a weather satellite receiver / Mohd Fauzi Abd Rashid - Abd Rashid, Mohd Fauzi (1995)
This paper reports a method of drive and control of an antenna. This antenna is driven and controlled by two (2) units of DC motors complete with electronics circuit control which facilitates the start, forward movement, reverse movement, speed control and step movement. In this project a set of motor and controller is used for azimuth direction and the other set is for elevation direction. The motor torque and its power is much dependent on the antenna weight and gear system design